Childhood, adolescence and sexual rights in Brazil: conservatism in blue and pink - Penante, Ana Paula Cruz; Sousa, Adrianyce A. Silva de (Argumentum, 2023)
This article analyses the political disputes between the social forces of society and public power, from the perspective of sexual rights, by opening a debate on the sexual rights of children and adolescents in the Brazilian context. Through exploratory research, we carried out a documentary analysis of the sexual rights of children and adolescents. We identified that, within the framework of capitalist society, the Brazilian debate on the sexual rights of children and adolescents is tensioned from two central perspectives: the first, imbued by the logic of guardianship, seeks to restrict the exercise of sexuality to adults; and the second, based on the paradigm of human rights, seeks to ensure the right to the full development of children and adolescents, understanding sexuality as part of the process of socialisation and the make-up of the human race.Keywords: Children and adolescence. Sexual rights. Human rights. Emancipation.